Hepatic Artery Denervation and Liver Cryodestruction Effects on Biochemical Indices Under Experimental Cirrhosis - Chizh, N. A.; Belochkina, I. V.; Sandomirsky, B. P. (Problems of Cryobiology and Cryomedicine, 2007)
Efficiency of periarterial hepatic denervation and local cryodestruction of 10% liver mass was compared in the model of CCl4-induced diffusive rat liver injury. Hepatic artery was mechanically and surgically denervated. Results of blood serum biochemical studies (albumin, alanine-aminotransferase, aspartate-aminotransferase, thymol test) have demonstrated that all types of surgery contribute equally to an accelerated normalisation of studied biochemical indices within 2 observation months. A technical simplicity of hepatic artery cryodestruction performance is noted as this denervation method advantage.